Genetic dissection of cold tolerance in sorghum (Sorghum bicolor L. Moench) - Chakrabarty, Subhadra; Justus Liebig University Giessen (My University, 2022)
Sorghum (Sorghum bicolor L. Moench), the 5th most important cereal crop belongs to the Poaceae grass family. According to records, it originated around 7000-5000 BC in the north-eastern part of Africa from where it traveled across the different parts of Africa, the middle east, India, China and eventually Americas, Australia, and finally Europe. As a result of multiple complex genomic interactions and selection, pressure can be broadly subdivided into the botanical classification of S. halepense, S. propinquum, and S. bicolor, and classification of cultivated forms of S. bicolor subsp. bicolor into five races, namely bicolor, guinea, caudatum, kafir, and durra. It is mainly grown in the lowlands and semi-arid regions of the tropics and subtropics and has been adapted to various contrasting environments for different end-products leading to an increase in morphological and genetic diversity. For example, in African countries, it is primarily grown as food grain and stalk, and leaves are valued as forage and building material. In the USA, its mainly used for livestock feed and ethanol production, whereas, in China, it is popular for manufacturing traditional alcoholic beverages. Sorghum’s remarkable ability to survive and produce yields under extreme climatic conditions compared to most other grain crops makes it an important 'failsafe' source of food, feed, fiber, and fuel in the global agroecosystem. Future projections regarding changing climate and its negative effect on yield traits, highlight the urgency to harness new genetic resources and the ability of breeding programs to develop the required adaptations promptly. Sorghum has numerous agro- ecological advantages over other crops like maize when it comes to temperate climates. But few of the biggest hurdles for sorghum adaptation to cooler climates are juvenile and reproductive cold stress. The present study reported a genetic characterization of the diverse, previously uncharacterized S.bicolor collection of the Uganda National Genebank, representing different agro-ecological zones of the country. High-resolution genotyping using reduced representation sequencing was used to characterize the material and study population genetics. More than 3000 S. bicolor accessions were genotyped using a panel of around 20,000 genome-wide DArTseq SNP markers and co-analyzed with a global sorghum collection genotyped previously with the same panel of markers for genetic diversity analysis and studying different interesting traits. The results revealed the presence of extensive genetic and racial diversity in predominantly admixed accessions and a unique, genetically isolated group of accessions from the southwestern Ugandan highlands, a region which low temperatures which potentially harbors genes of interest for breeding of sorghum in Germany and other temperate climate zones. A representative core set of the novel Ugandan sorghum germplasm was analyzed to study juvenile cold tolerance. Data was collected from multi-year field trials and controlled climate chamber experiments. Genome-wide association studies were used to identify genomic regions involved in adaptation to cooler climatic conditions that could be of interest for the expansion of sorghum production into temperate latitudes. This thesis can be considered a case study to illustrate the potential of genebank genomics to screen valuable, underutilized germplasm collections to evaluate various biological and agro-economical traits and alleles. While farmers can avoid early-stage cold stress by later sowing (albeit at the expense of maturity and yield potential), there is no escape strategy for reproductive stage cold stress. This trait was analysed in another broad diversity panel consisting of 330 inbred lines of different origin, types of use, and subspecies from multi-location field trials including tropical high-altitude and temperate environments. In this study, several significant marker-trait associations were identified. This was further combined with local LD analysis, previously curated QTL data, and synteny to potential candidate genes in rice and maize to narrow down to interesting marker-trait associations to specific genomic regions involved in cold stress response. This thesis can be considered a basis for selecting accessions for genetic diversity preservation and management, utilization in breeding programs, and establishing genetic relationships with other existing germplasm collections. The results provide important new insights for adaptive crop breeding in the face of climate change and the expansion of sorghum production to different regions. This will facilitate sorghum from being a "plant of the future" to transforming into a real-life major agricultural alternative.
Keywords: sorghum; genetics; cold tolerance; ddc:630